The Influence of The Big Book Media Has The Character of Conservation in Early Reading - Otang Kurniaman; Nugraheti Sismulyasih Sb (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
The big book media with the character of conservation is the development of learning media adapted to the character of the child in early reading. The purpose of this study was to see the effect of big book media on conservation characteristics in early reading in the first grade of SD Labschool Unnes using a quasi-experimental method with a pretest-posttest design with one research class without any comparison class with data analysis using SPSS 17. The results of the study were correlation correlation pretest and posttest of 0.757 with a determinant coefficient or R Square of 0.573 that the big book media conservation character influences early reading with a magnitude of 0.548, to test the significance with Fcount = 22.821 with a significance level of 0.000 < 0.005, so the significant influence of big book media on conservation early reading skills, to answer the research hypothesis then tested by looking at constant posttest of 48.861 while the regression value of 0.561 can be interpreted that the regression coefficient is positive, then the research hypothesis is answered by the conclusion that the media is big book conservation characteristics affect early reading.